ChemInform Abstract: Microwave‐Assisted Synthesis of Asymmetric Disulfides. Issue 6 (February 2015) - Lu, Xiaogang; Wang, Hongmei; Gao, Runli; Sun, Daoming; Bi, Xiaojing
Abstract Tertiary alkyl halides and aryl halides fail to react.